Peptide Mediated Brain Delivery of Nano- and Submicroparticles: A Synergistic Approach - McCully, Mark; Sanchez-Navarro, Macarena; Teixido, Meritxell; Giralt, Ernest (Current Pharmaceutical Design, 2018)
The brain is a complex, regulated organ with a highly controlled access mechanism: The Blood-Brain Barrier (BBB). The selectivity of this barrier is a double-edged sword, being both its greatest strength and weakness. This weakness is evident when trying to target therapeutics against diseases within the brain. Diseases such as metastatic brain cancer have extremely poor prognosis due to the poor permeability of many therapeutics across the BBB. Peptides can be designed to target BBB receptors and gain access to the brain by transcytosis. These peptides (known as BBB-shuttles) can carry compounds, usually excluded from the brain, across the BBB. BBB-shuttles are limited by poor loading of therapeutics and degradation of the peptide and cargo. Likewise, nano- submicro- and microparticles can be fine-tuned to limit their degradation and with high loading of therapeutics. However, most nano- and microparticles' core materials completely lack efficient targeting, with a few selected materials able to cross the BBB passively. Combining the selectivity of peptides with the high loading potential of nano-, microparticles offers an exciting strategy to develop novel, targeted therapeutics towards many brain disorders and diseases. Nevertheless, at present the field is diverse, in both scope and nomenclature, often with competing or contradictory names. In this review, we will try to address some of these issues and evaluate the current state of peptide mediated nano,-microparticle transport to the brain, analyzing delivery vehicle type and peptide design, the two key components that must act synergistically for optimal therapeutic impact.
Keywords: nanoconstruct